Universal geometric transformation method PGT for aircraft design - Nikolsky, A. (My University, 2018)
The original technique for CAD/ CAE applications of generating aerodynamic shapes is developed. The universal geometric 'parent function/generating functions' transformation method, PGT, is proposed which creates the compact design space covering the entire class of wireframe contours for the design of basic aircraft elements